SYSTEMATIC LITERATURE REVIEW: PEMAHAMAN KONSEP PKN PADA SISWA SEKOLAH DASAR - Arlinda, Rossy; Zulparis (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This Systematic Literature Review aims to synthesize several published studies related to the understanding of the concept of Civics in elementary school students. Therefore, this study focuses on "Understanding the Concept of Civics in Elementary School Students". The method used is the article selection method, inclusion criteria and a more objective analysis method. In the article selection procedure, the PRISMA article selection steps, or what is known as the PRISMA flow diagram recommended for SLR, obtained 806 articles and journals. Then a review of journals related to the understanding of the concept of Civics in elementary school students was carried out so that 62 related articles were obtained discussing the understanding of the concept of Civics in elementary school students.